Influence of nanoclay in viscosity graded asphalt binder at different test temperatures - Sukhija M.; Saboo N. (My University, 2025)
Nanotechnology has been progressively insinuating into the research field of asphalt binder modification. However, studies on various characteristics of nanoclay modified binder including resistance to ageing, temperature susceptibility and rheological performance, are still obscure. This study focuses on studying the efficacy of nanoclay modification on the properties of viscosity graded (VG 30) asphalt binder. High shear mixer was employed for the modification of different dosage (2-6%) of nanoclay to counteract the above mentioned performance characteristics. Conventional tests along with the rheological performance were evaluated for nanoclay modified and unmodified binders. Master curves at 20°C and 60°C obtained from the frequency sweep (FS) test data revealed that improvement in rheological properties is more obvious at lower frequencies. Different Indices were evaluated analyzing FS data across different temperatures. A satisfactory and translucent level of modification was observed from Modification Index. Alongside, decrease in ageing index confirms the resistance to ageing potential of nanoclay modified asphalt binder. A noticeable change in black curve was observed for 6% NC modified asphalt binder while 2% and 4% NC modified asphalt binder was found to be less significant. However, the improvement with 2% and 4% NC inclusion was still higher than VG 30. From the fabrication of nanoclay modified asphalt binder to the rheological characterization process, this study confirms that nanoclay holds great prospective in alleviating the performance of VG 30 binder at all the test temperatures. © 2021 Taylor & Francis Group, London.